2011
DOI: 10.1002/adfm.201101557
|View full text |Cite
|
Sign up to set email alerts
|

Novel Triclosan-Bound Hybrid-Silica Nanoparticles and their Enhanced Antimicrobial Properties

Abstract: The design and synthesis of novel hybrid‐silica nanoparticles (NPs) containing the FDA‐approved antimicrobial triclosan (Irgasan) covalently linked within the inorganic matrix for its controlled, slow release upon interaction, is reported. The NPs are in the range of 130 ± 30 nm in diameter, with a smooth and spherical morphology. Characterization of the hybrid‐silica NPs containing triclosan, namely T‐SNPs, and their appropriate linkers is accomplished by microscopic and spectroscopic techniques. Preliminary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…[ 2 ] We also reported that a close physical proximity/ contact, i.e., a direct interaction between the bacteria and particle components, is critical for the observed antimicrobial activity. [ 2 ] Encouraged by this observation, we proceeded to characterize the more advanced NPs (NH 2 -T-SNPs) and evaluated their antimicrobial activity and began to elucidate the biochemical mechanism of action of these antimicrobial NPs. show that for both bacteria, NH 2 -T-SNPs caused a reduction in growth in a dose-dependent manner, as did the T-SNPs, but with a reduced MBC, 5 μ g mL − 1 for both pathogens, instead of the former 10 μ g mL − 1 value for T-SNPs.…”
Section: Antimicrobial Activity Of Nh 2 -T-snpsmentioning
confidence: 94%
See 4 more Smart Citations
“…[ 2 ] We also reported that a close physical proximity/ contact, i.e., a direct interaction between the bacteria and particle components, is critical for the observed antimicrobial activity. [ 2 ] Encouraged by this observation, we proceeded to characterize the more advanced NPs (NH 2 -T-SNPs) and evaluated their antimicrobial activity and began to elucidate the biochemical mechanism of action of these antimicrobial NPs. show that for both bacteria, NH 2 -T-SNPs caused a reduction in growth in a dose-dependent manner, as did the T-SNPs, but with a reduced MBC, 5 μ g mL − 1 for both pathogens, instead of the former 10 μ g mL − 1 value for T-SNPs.…”
Section: Antimicrobial Activity Of Nh 2 -T-snpsmentioning
confidence: 94%
“…In our previous study, [ 2 ] we showed that T-SNPs posses superior antimicrobial activity compared to the free biocide (an increase of 5-6 log in killing capacity). In the current work, we continued to explore the aforementioned properties with second generation NPs that contained an outer polycationic shell containing polyNH 2 species.…”
Section: Nh 2 -T-snps' Synthesis and Characterizationmentioning
confidence: 98%
See 3 more Smart Citations